Review of the genus Isodemis Diakonoff (Lepidoptera, Tortricidae) from China, with description of three new species - Sun, Yinghui (Pensoft Publishers, 2011)
Abstract. The genus Isodemis Diakonoff, 1952 in China is reviewed, with seven species recognized. Three new species are described: Isodemis quadrata sp. n., Isodemis guangxiensis sp. n. and Isodemis hainanensis sp. n. The female of Isodemis stenotera Diakonoff, 1983 is described for the first time. Variation within Isodemis illiberalis (Meyrick, 1918) and Isodemis stenotera is briefly discussed. Images of the adults and genitalia are provided, along with a key to the described species.